Metabolite Fingerprinting Eleutherine palmifolia (L.) Merr. Using UPLC-QTOF-MS/MS - Roihatul Mutiah; Weka Sidha Bhagawan; Burhan Ma'arif; Jauhar Maknun Septaza Rahmandika (Faculty of Pharmacy, Universitas Gadjah Mada, 2019)
Eleutherine palmifolia (L.) Merr. (E. palmifolia) is an Indonesian native plant that has the potential to be developed into phytopharmaca. The differences in growth locations are thought to cause variation in the content of metabolite compounds which affect differences in pharmacological activity. This study aims to determine the profile of metabolites E. palmifolia bulb from several regions in Indonesia. The samples were collected from six different locations, namely East Java, Central Java, West Java, East Borneo, Central Borneo, and South Borneo. Sample extraction was carried out using Ultrasonic Assisted Extraction (UAE) method with 96% ethanol. The analysis of the content of metabolites was carried out using UPLC-QTOF-MS/MS with a stationary phase column C18 (Okta Decyl Silica), mobile phase mixture of formic acid /water 0.1/99.9 (v/v), and formic acid/acetonitrile 0,1/99,9 (v/v). The results of the analysis were interpreted using software Masslynx and continued with chemometric analysis using the method Principle Component Analysis (PCA). The results showed that there were differences in the content of the metabolite compounds in E. palmifolia bulb originating from six different regions.